A new design equation to estimate the axial compressive strength of circular concrete-filled steel tubular stub columns. (December 2022) - Lai, Zhichao; Jiang, Haonan; Cai, Yancheng
Abstract: This paper proposes a new design equation for circular concrete-filled steel tubular (CCFST) stub columns. A database consisting of 394 CCFST stub column tests are first compiled. Finite element (FE) analysis is then performed to generate 174 new results to cover the gaps in the database. Based on these, the correlations between the strength enhancement index and the tube diameter-to-thickness ratio, section slenderness, and relative strength factor are investigated. The experimental and FE ultimate loads are used to assess the accuracy of the existing codified strength predictions. Overall, it is found that the European Code (EC 4) provides more accurate strength predictions than the American (AISC 360-16) and Japanese (AIJ) codes, but is unconservative for high-strength CCFST short columns. A new unified design equation by incorporating the effect of ξ is then proposed. The strengths predicted by the proposed equation are comparably accurate as those predicted by EC 4. The proposed equation allows a fast and convenient estimation of the axial compressive strength of CCFST stub columns, with no need to calculate or classify the section slenderness of CCFST stub columns. Hence, it is recommended for practical strength estimation.